Use of The Problem Based Instruction Model on Activities and Results of Integrated Thematic Learning Students in Class V - Sonia Septi Gamandari (Postgraduate School, Universitas Negeri Padang, 2019)
This research is motivated by the lack of teachers' ability to design the use of problem based instruction models on students' thematic learning outcomes, planning the use of problem based instruction models for students' thematic learning outcomes. The purpose of this study is to increase the use of problem based instruction models for student thematic learning outcomes problem based instruction model of the results of students' thematic learning and improving student learning outcomes using the Problem Based Instruction Model. This type of research is a field research with a descriptive qualitative method. The results showed that the use of the Problem Based Instruction model in the teaching and learning process can improve student learning outcomes. Conclusion of the form of planning using the Model Problem Based Instruction The teacher has prepared the RPP so that learning is more directed. Use of Problem Based Instruction Models can improve student learning outcomes the teacher in using the model based instruction problem the time used is very limited